Ekstraksi elemen kemasan basreng ikan menggunakan metode rough set berbasis Kansei Engineering - Novi Purnama Sari; Annisa Putri Febriyani; Wiwi Prastiwinarti (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
This study employs the Rough Set method based on Kansei Engineering to analyze the packaging design elements of fish fried meatballs. The purpose of this study is to identify design elements that align with consumer preferences. The method involved collecting consumer preference data through Kansei Engineering and processing it using Rough Set analysis. The results recommended a packaging design with the highest Laplace value of 0.7500 and a support size of 2. The recommended packaging includes multilayer material, standing pouch type, sealing closure system, additional features such as ziplock and hanging hole, modern design style, sans-serif typography, design elements featuring images and illustrations, a fun color scheme, medium size, and direct print on the material surface. This study demonstrates that Kansei Engineering can produce packaging designs that match consumer preferences through quantitative data analysis.